Specially Designed Instruction in Middle and High School Co-taught Classrooms. Issue 6 (3rd September 2020) - Hedin, Laura R.; Conderman, Greg; Gerzel-Short, Lydia; Liberty, Lisa
Abstract: Students with disabilities are increasingly participating in co-taught classes where they have access to the general curriculum. However, researchers have discovered that co-teaching often resembles solo teaching and does not include specially designed instruction shown to be effective for students with disabilities. How can middle and secondary co-teachers improve their instructional effectiveness? This article describes specially designed instruction, associated with high leverage practices, and provides ways middle and high school co-teachers can improve their co-teaching effectiveness.